2021
DOI: 10.3390/ijerph181910417
|View full text |Cite
|
Sign up to set email alerts
|

Sprint Variables Are Associated with the Odds Ratios of Non-Contact Injuries in Professional Soccer Players

Abstract: Significant evidence has emerged that a high volume of sprinting during training is associated with an increased risk of non-contact injuries in professional soccer players. Training load has been reported as a modifiable risk factor for successive injury in soccer. Sprint workload measures and non-contact injuries were recorded weekly in twenty-one professional soccer players over a one season period. Odds ratio (OR) and relative risk (RR) were calculated based on the weeks of high and low load of total dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The nervous system is responsible for controlling body position and movements through feedback and feed forward mechanisms. It is well established that dynamic stability of the ankle joint is usually controlled by the feed forward mechanism, which uses the visual, auditory, and tactile senses, as well as previous experience and internal models, to maintain body position and movements [3,[12][13][14]. The changes in neuromuscular control could affect postural stability in patients with chronic ankle instability [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nervous system is responsible for controlling body position and movements through feedback and feed forward mechanisms. It is well established that dynamic stability of the ankle joint is usually controlled by the feed forward mechanism, which uses the visual, auditory, and tactile senses, as well as previous experience and internal models, to maintain body position and movements [3,[12][13][14]. The changes in neuromuscular control could affect postural stability in patients with chronic ankle instability [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that with FAI, feed forward neuromuscular control is more important and can be influenced by exercise interventions [17,18]. Balance exercises are one of the significant interventions to reduce ankle injuries and rehabilitation [14,19]. Wobble or balance board exercises are usually effective in the rehabilitation of those with ankle instability problems [20].…”
Section: Introductionmentioning
confidence: 99%
“…The criteria to define starters and non-starters were assessed week by week to a player’s attendance time in three consecutive matches (≥60 min in each match), while non-starters were considered those who did not achieve this duration based on previous studies ( Martins et al, 2021 ; Nobari et al, 2020 , 2021c ; Oliveira et al, 2021a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…The following stages were performed in the BL calculation for each acceleration level: initialize the BL count to 0; calculate the magnitude of the acceleration vector (V) for the current acceleration (V = ax2 + ay2 + az2); and normalize the magnitude vector (NV) by subtracting a national 1 G (NV = V − 1.0 G). Following that, the unscaled BL (USBL) was calculated using the formula USBLC = NV + [NV3] [51]; after that, the scaled BL (SBLC) was computed using the accelerometer logging rate (100 HZ) and exercise factor (EF) (SBLC = USBLC/100/EF); finally, the final BL (BL = BL + SBLC) was determined [52]. BL had replaced the original GPSports.…”
Section: Data Collection By Wearable Inertial Measurement Unitmentioning
confidence: 99%
“…In this study, BL was used as the criterion for the training load. For calculating training load parameters in order [51]:…”
Section: Training Loadmentioning
confidence: 99%